Assessment of the risk of consuming milk/milk products contaminated with Listeria monocytogenes from the informal markets - Appiah, J. (University of Ghana, 2012)
Listeria monocytogenes is the causative organism of listeriosis, a debilitating and often fatal infection, which occurs mostly via food consumption. However, some foods such as dairy, probably due to their nutritious nature and handling characteristics, are more prone to contamination and thus are relatively more culpable. To prevent L. monocytogenes contamination of such products, it is critical to be insightful of listerial contamination routes in food processing environments. This study investigated L. monocytogenes contamination routes along the informal milk value chain from production to consumption. Microbiological methods according to the US/ FDA protocol (Hitchins, 1998) including chromogenic Listeria agar (ISO) OCLA use and biochemical methods including the Gram, Catalase and the Beta- haemolysis were employed to isolate L. monocytogenes from 304 samples of milk/ milk products. Results indicated that prevalence generally increased with repeated handling though it decreased with boiling (p<0.05). Prevalence in samples at production, retail (i.e. raw milk on the market), after boiling and fermentation were 42.1, 78.9, 18.4 and 59.2 percent respectively. Also 14.8, 57.9, 6.6 and 46.1 percent of samples had mean counts ≥100 CFU/ mL at production, at retail, after boiling and fermentation respectively (p<0.05). A Quantitative Risk Assessment indicated a higher exposure and probability of illness when raw milk at retail was consumed and the least when boiled milk was consumed. Crude Sensitivity Analysis also predicted the most effective mitigation strategy for exposure to be boiling. Hence boiling of raw milk was crucial to its safe consumption. However, with contamination at all stages of the value chain, it was important to emphasize on the hygiene regimen along the whole continuum as safety at one stage could very easily be undone by the lack of proper procedures at another.